Agronomy Character and Sinensetin Content of Several Java’s Tea Plant Accession (Orthosiphon stamineus) - Febjislami, Shalati; Melati, Maya; Kurniawati, Ani; Wahyu, Yudiwanti (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2018)
Java’s tea plants have efficacy to treat diabetes. Sinensetin is a chemical compound in Java’s tea that acts as diabetes medicine. The experiment objective was to study diversity of agronomy characters and sinensetin content of ex situ collections of Java’s tea from West, Central, and East Java regions. Java’s tea was harvested when population has flowering about 70% and tested sinensetin content on leaf part. The experiment was conducted with a completely randomized block design with 18 accessions and one control (purple flower accession). The result of study showed that there were significant differences in the accumulation of height plant increase while 8 weeks after planting, secondary branches and secondary branches internode number; leaf length, width and area index; average stems and leaf dry weight per 4.41 m2 and sinensetin levels among some accessions. Banyumas 1, Sumbersari and Kraksaan accessions have agronomy and production characters except for sinensetin levels were better than control (Leaf sinensetin levels based on leaf dry weight increased from low to medium but decreased in high category) Based on comparison between accession and leaf dry weight category, purple flower accession has higher sinensetin levels (0.043%) than another accession, but only reaches 43% of Indonesian Herbal Pharmacopoeia minimum standard (There were no significant differences in sinensetin accession production tested either by comparison of accession or accession categories). Keywords: ex situ, flower, Java’s tea, Orthosiphon aristatus, sinensetin